The immatures of Culicoides lacustris Ronderos (Diptera: Ceratopogonidae) - Anjos-Santos, Danielle; Funes, Amparo; Spinelli, Gustavo R.; Ronderos, María M. (Zootaxa, 2014)
Larva and pupa of the Patagonian species Culicoides lacustris Ronderos are described in detail with phase-contrast microscope at oil immersion and scanning electron microscope. Studied specimens were collected in a wetland, alongside to the Provincial Route 12, between the cities of Esquel and Gualjaina in the Chubut Province. They are compared with the more similar congener, Culicoides venezuelensis Ortiz & Mirsa.